Fetomaternal hemorrhage: Evidence from a multihospital healthcare system that up to 40% of severe cases are missed. Issue 1 (21st October 2021) - Carr, Nicholas R.; Henry, Erick; Bahr, Timothy M.; Ohls, Robin K.; Page, Jessica M.; Ilstrup, Sarah J.; Christensen, Robert D.
Abstract: Background: We previously reported fetomaternal hemorrhage (FMH) in 1/9160 births, and only one neonatal death from FMH among 219, 853 births. Recent reports indicate FMH is not uncommon among stillbirths. Consequently, we speculated we were missing cases among early neonatal deaths. We began a new FMH initiative to determine the current incidence. Methods: We analyzed births from 2011 to 2020 where FMH was diagnosed. We also evaluated potential cases among neonates receiving an emergent transfusion just after birth, whose mothers were not tested for FMH. Results: Among 297, 403 births, 1375 mothers were tested for FMH (1/216 births). Fourteen percent tested positive (1/1599 births). Of those, we found 25 with clinical and laboratory evidence of FMH adversely affecting the neonate. Twenty‐one received one or more emergency transfusions on the day of birth; all but two lived. We found 17 others who received an emergency transfusion on the day of birth where FMH was not tested for, but was likely; eight of those died. The 42 severe (proven + probable) cases equate to 1/7081 births. We judged that 10 of the 42 had an acute FMH, and in the others it likely had more than a day before birth. Conclusions: We estimate that we fail to diagnose >40% of our severe FMH cases. Needed improvements include (1) education to request maternal FMH testing when neonates are born anemic, (2) education on false‐negative FMH tests, and (3) improved FMH communications between neonatology, obstetrics, and blood bank.